(untitled) (Altre Modernità, 2010)
In Northern Ireland, the conflict between Unionists and Republicans, Catholic and Protestants saw its peak during the ‘Troubles’ of 1969-1993. Today, after four decades of physical violence, the peace process has reached a successful ending and a war of words has finally replaced real war. To study how this move from arms to political debate occurred, a written corpus was collected, comprising annual party conference speeches given during the years 1993-2004 by the leaders of the two main and opposed political parties of Northern Ireland, Gerry Adams and Ian Paisley. By comparing these texts, it was possible to observe the development of their discourse from a short-term diachronic perspective. A Critical Discourse Analysis approach is considered particularly suitable for dealing with political speeches, but contributions from different fields and disciplines are also considered. The discourse analysis of the texts collected is supported by computer-aided analysis. Two aspects are being focussed on, in particular: 1) the use of same/different linguistic resources by the same orators to discuss same/different subjects over the years; and 2) the overall influence of language on politics, i.e. how words are used to exercise power. It is hoped that the present study may help clarify aspects of the evolution of political discourse in Northern Ireland, in general, and of the argumentative skills and strategies of the above two politicians, in particular.